Bis‐Tridentate Ir(III) Metal Phosphors for Efficient Deep‐Blue Organic Light‐Emitting Diodes. Issue 33 (21st June 2017) - Kuo, Hsin‐Hung; Chen, Yi‐Ting; Devereux, Leon R.; Wu, Chung‐Chih; Fox, Mark A.; Kuei, Chu‐Yun; Chi, Yun; Lee, Gene‐Hsiang
Abstract : Emissive Ir(III) metal complexes possessing two tridentate chelates (bis‐tridentate) are known to be more robust compared to those with three bidentate chelates (tris‐bidentate). Here, the deep‐blue‐emitting, bis‐tridentate Ir(III) metal phosphors bearing both the dicarbene pincer ancillary such as 2, 6‐diimidazolylidene benzene and the 6‐pyrazolyl‐2‐phenoxylpyridine chromophoric chelate are synthesized. A deep‐blue organic light‐emitting diode from one phosphor exhibits Commission Internationale de l'Eclairage (CIE( x, y ) ) coordinates of (0.15, 0.17) with maximum external quantum efficiency (max. EQE) of 20.7% and EQE = 14.6% at the practical brightness of 100 cd m −2 . Abstract : A deep‐blue organic light‐emitting diode (OLED) from one bis‐tridentate Ir(III) phosphor5 exhibits CIE( x, y ) coordinates of (0.15, 0.17) with maximum external quantum efficiency (max. EQE) of 20.7% and EQE = 14.6% at the practical brightness of 100 cd m −2 .